Impact of Salinity and Sodicity on Crop Growth and Physicochemical Properties of Some Aridisol and Vertisol Soils in Sudan: A Review - Mustafa, Mukhtar Ahmed (University of Khartoum Journal of Agricultural Sciences, 2023)
Comprehensive field and laboratory studies were undertaken to investigate the performance of some crops on salt-affected soils in Sudan. To separate salinity and sodicity indicators some laboratory studies were conducted on soils equilibrated with mixed NaCl-CaCl 2 solutions. The relative hydraulic conductivity (RHC) or diffusivity increased with increase in total salt concentration (C) and decrease in exchangeable sodium percentage (ESP). A dispersion index (DI), a swelling index (SI), shrinkage volume and modulus of rupture increased with increase in ESP and decrease in C. The data showed a highly significant linear decrease in RHC with increase in DI or SI. The threshold salt concentrations (THC), which gave 75% of the highest RHC, and ESP relationships, were obtained for samples from an Aridisol and a Vertisol soils.. The salinity profile obtained after intermittent leaching with water suggested the presence of a desalinized zone followed by a salinized one with the highest salt concentration below the wetting front. The depth of the desalinized zone increased significantly with increase of the amount of water stored (r2 = 0.968) and the length of the wetting front (r2 = 0.974). Soil amendments promoted salt leaching in the following order: Sand> chicken manure> water hyacinth> gypsum> dry sewage> farm yard manure> control. Cumulative evaporation (E) for the various amendments